Parental Unemployment and Adolescents' Academic Performance - Nick Drydakis (Institute of Labor Economics (IZA), 2023)
During the Great Recession, the increase in Greece's unemployment rate was the highest in the European Union. However, there exists no multivariate study which has assessed the association between parental unemployment and adolescents' grades. The study utilised panel data from the same upper high schools in the periods 2011–2013 and 2017–2019 to assess whether the grades of adolescents were associated with parental unemployment. The exogeneity of parental unemployment with respect to adolescents' grade was confirmed. The analysis revealed that parental unemployment was associated with a decline in adolescents' grades. Periods of economic decline, i.e. in 2011–2013, were found to be associated with deterioration in adolescents' grades. Moreover, during periods of economic decline, parental unemployment was associated with a deterioration in adolescents' grades. Furthermore, parental unemployment was associated with lower adolescents' grades for those households that were not homeowners and whose schools were located in working-class areas. The outcomes were found to be robust, even after including information for government expenditure on education and social protection. The potential long-lasting effects of parental unemployment on children's human capital should be considered by policymakers, as should educational interventions to support households experiencing adverse economic conditions.
Keywords: E24; J6; I24; J13; 330; economic recession; parental unemployment; grades; adolescents; academic performance